The Relationship Of Knowledge And Attitude Of Mothers With The Success Of Exclusive Breast Milk - Sri Wulan (Fakultas Keperawatan dan Fisioterapi Institut Kesehatan Medistra Lubuk Pakam, 2022)
Exclusive breastfeeding for babies is important because breast milk is the main source of food for the baby's needs but at this time many mothers who after giving birth do not succeed in giving breast milk because of factors such as uneven milk production, mothers who work outside home or because the mother's knowledge and attitudes are low so that the success rate in breastfeeding is very minimal. The purpose of this study was to determine how the relationship between knowledge and attitudes of mothers with the success of exclusive breastfeeding. This research is a quantitative research with cross sectional design. The samples used were mothers who had babies aged 0-6 months as many as 22 people. The sampling technique used total sampling technique, the test used was the Chi-Square test with the provisions of the p value <0.05. The results showed that there was a significant relationship between knowledge and the success of breastfeeding with a p value of 0.00<0.05 and there was a relationship between attitudes and the success of breastfeeding with a p value of 0.02<0.05. It is recommended to mothers who are breastfeeding to be able to give their breast milk exclusively because breast milk has complete nutritional content for the baby's needs